Progressive Resistance Training to Impact Physical Fitness and Body Weight in Pancreatic Cancer Patients: A Randomized Controlled Trial. Issue 2 (February 2019) - Wiskemann, Joachim; Clauss, Dorothea; Tjaden, Christine; Hackert, Thilo; Schneider, Lutz; Ulrich, Cornelia M.; Steindorf, Karen
Abstract : Objectives: Maintaining or improving muscle mass and muscle strength is an important treatment goal in pancreatic cancer (PC) patients because of high risk of cachexia. Therefore, we assessed feasibility and effectivity of a 6-month progressive resistance training (RT) in PC patients within a randomized controlled trial. Methods: Sixty-five PC patients were randomly assigned to either supervised progressive RT (RT1), home-based RT (RT2), or usual care control group (CON). Both exercise groups performed training 2 times per week for 6 months. Muscle strength for knee, elbow, and hip extensors and flexors and cardiorespiratory fitness and body weight were assessed before and after the intervention period. Results: Of 65 patients, 43 patients were analyzed. Adherence rates were 64.1% (RT1) and 78.4% (RT2) of the prescribed training sessions. RT1 showed significant improvements in elbow flexor/extensor muscle strength and in maximal work load versus CON and RT2 ( P < 0.05). Further, knee extensors were significantly improved for RT1 versus CON ( P < 0.05). Body weight revealed no significant group differences over time. Conclusions: Progressive RT was feasible in PC patients and improved muscle strength with significant results for some muscle groups. Supervised RT seemed to be more effective than home-based RT.